Chiral three-dimensional lattices with tunable Poisson's ratio. (8th April 2016) - Ha, Chan Soo; Plesha, Michael E; Lakes, Roderic S
Abstract: Chiral three-dimensional cubic lattices are developed with rigid cubical nodules and analyzed via finite element analysis. The lattices exhibit geometry dependent Poisson's ratio that can be tuned to negative values. Poisson's ratio tends to zero as the cubes become further apart. The lattices exhibit stretch–twist coupling. Such coupling cannot occur in a classical elastic continuum but it can occur in a chiral Cosserat solid.